DIGITIZATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN ENHANCING STUDENT LEARNING MOTIVATION AT SMP NU SUNAN GIRI KEPANJEN - Muhammad Arif Nasruddin, Widiatul Fauziah; Solihin (The Center for Language Development, Mataram State Islamic University., 2024)
The widespread adoption of technological advancements today has brought changes to many aspects of society, including education. The Ministry of Education and Culture has sought to adjust teaching strategies to accommodate new technological advancements, such as internet usage. SMP NU Sunan Giri Kepanjen, which has implemented digital learning, follows these guidelines. This policy is developed with consideration for the latest technological advancements in the field of education, particularly in Islamic Religious Education. This study aims to assess the level of digitization in Islamic Religious Education (PAI) learning at SMP NU Sunan Giri Kepanjen; to examine student learning motivation in PAI classes at SMP NU Sunan Giri Kepanjen; and to identify the factors that facilitate or hinder the digitization of Islamic Religious Education learning at SMP NU Sunan Giri Kepanjen. The research method used in this study is descriptive qualitative, with data collected through documentation, in-depth interviews, and observation. The research found that digitization in Islamic Religious Education learning can enhance students' motivation to learn. The digital tools used include educational videos and presentations using digital devices.